2018
DOI: 10.18203/2320-1770.ijrcog20183345
|View full text |Cite
|
Sign up to set email alerts
|

A study of maternal near miss cases in tertiary health centre in north India

Abstract: Background: Maternal near miss is defined as woman who nearly died but survived a complication that occurred during pregnancy, childbirth or within 42 days of termination of pregnancy.Methods: It was one-and-a-half-year prospective study from April 2016 to September 2017 conducted in the department of Obstetrics and Gynecology, Government Medical College, Patiala. The causes of maternal near miss based on WHO 2010 Near Miss criteria were studied.Results: In the present study out of total deliveries of 6166, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…As in other studies, hemorrhage was reported as a leading cause of death. 7,10 Prompt referral, adequate transportation, active management of the third stage of labor, and postpartum care must be strengthened to reduce MNM and maternal deaths due to PPH and sepsis. Existing comorbidities such as cardiac disease and liver disease were also found to have high mortality index.…”
Section: Discussionmentioning
confidence: 99%
“…As in other studies, hemorrhage was reported as a leading cause of death. 7,10 Prompt referral, adequate transportation, active management of the third stage of labor, and postpartum care must be strengthened to reduce MNM and maternal deaths due to PPH and sepsis. Existing comorbidities such as cardiac disease and liver disease were also found to have high mortality index.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhage was the major cause (43.5%) of maternal near-miss followed by severe anaemia (15.38%), rupture uterus (15.38%), pre-eclampsia / eclampsia (12.82%), sepsis (5.12%), complicated malaria (5.12%) and hepatitis (2.56%) were recorded. 8 Most common direct complications of pregnancy were hemorrhage (26%), eclampsia (18.7%), sepsis (9.8%), ruptured uterus (4%) and obstructed labour (3.2%) as per study of Kaur et al 9 The indirect causes were recorded as anaemia (34.1%), respiratory disease (4%), liver disease (5.7%) and heart disease (1.6%).…”
Section: Introductionmentioning
confidence: 96%